2009
DOI: 10.1007/s10549-009-0347-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in genes of the fatty acid synthesis pathway and breast cancer risk

Abstract: Fatty acid synthase (FAS) is the major enzyme of lipogenesis. It catalyzes the NADPH-dependent condensation of acetyl-CoA and malonyl-CoA to produce palmitic acid. Transcription of the FAS gene is controlled synergistically by the transcription factors ChREBP (carbohydrate response element-binding protein), which is induced by glucose, and SREBP-1 (sterol response element-binding protein-1), which is stimulated by insulin through the PI3K/Akt signal transduction pathway. We investigated whether the genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…One previous study has shown no relationship between single-nucleotide polymorphism of either ChREBP or FASN and breast cancer risk (Campa et al , 2009). The differential staining between normal adjacent and malignant tissue, as well as the clear increase in de novo expression of ChREBP protein with malignant progression, therefore suggests that local rather than genomic changes in ChREBP may have a role in driving tumourigenesis.…”
Section: Discussionmentioning
confidence: 97%
“…One previous study has shown no relationship between single-nucleotide polymorphism of either ChREBP or FASN and breast cancer risk (Campa et al , 2009). The differential staining between normal adjacent and malignant tissue, as well as the clear increase in de novo expression of ChREBP protein with malignant progression, therefore suggests that local rather than genomic changes in ChREBP may have a role in driving tumourigenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Repeated quality control genotypes (8% of the total) showed an average concordance of 99.9%. More details on the genotyping methods can be found elsewhere [36], [46], [47]. PCR plates were read on an ABI PRISM 7900HT instrument (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…al. (Campa et al, 2009) investigated 20 SNPs in the ChREBP, SREBP-1, and FASN genes of breast cancer and control patients from a Western European population. ChREBP and SREBP-1 are transcription factors known to directly regulate enzymes of the fatty acid synthesis pathway, including FASN (Eberle et al, 2004).…”
Section: Genetic Variation Modifies Fatty Acid Metabolismmentioning
confidence: 99%
“…They found no significant associations between any of the 20 SNPs and overall breast cancer risk by age or menopausal status. However, 2 SNPs in the FASN gene, rs1140616 and FAS_A0866, were found to be significantly associated with a moderately higher BMI in younger/pre-menopausal women and a marginally lower BMI in older/post-menopausal women, respectively (Campa et al, 2009). Another group (Schleinitz et al, 2010) identified 35 SNPs from sequencing the FASN gene in a German population of adults and children.…”
Section: Genetic Variation Modifies Fatty Acid Metabolismmentioning
confidence: 99%